Communication—Binder Effects on Cycling Performance of High Areal Capacity SPAN Electrodes. Issue 11 (2nd November 2021) - Wu, Zhaohui; Liu, Haodong; Yu, Sicen; Liu, Ping
Abstract : We report here the binder effect on the cycling performance of high areal capacity sulfurized polyacrylonitrile (SPAN) cathodes (>6 mAh cm −2 ). Thick SPAN cathode with the polyvinylidene difluoride (PVdF) binder only maintains 66.7% capacity at 60th cycle. Mechanical integrity failure is responsible for the decay indicated by morphological and mechanical analysis. Carboxymethylcellulose (CMC) markably improves the corresponding capacity retention to 94.5%. Stable cycling of low porosity (30%) cathode is also enabled by binder optimization. This work shows the importance of binder choice on thick SPAN cathodes and paves the way for high energy density Li∣∣SPAN cell.